Study of Wireless Sensor Network Location Algorithm and Data Collection Protocol - Han, Weimin; Li, Shijun; Li, Weidong (International Journal of Online and Biomedical Engineering (iJOE), 2016)
It is deduced that the network life time is inversely proportional to the zone area of the collection data that each sink is responsible for. That is to say, when the zone area in the charge of a sink is smaller, the average load of nodes distributed in this area and the energy consumption are smaller, while the network life time is longer. MSGP protocol is proposed, with several round cluster head candidate zones, fixed member zones and public zones being delimited to make approximately uniform clustering. The cluster head is responsible for collecting a meaningful event in the cluster, making data fusion and then forwarding it to sink. Multi-sinks move according to the zone division rules and the rule of free movement. Specific analysis is made from three aspects of data direction, single round data collection of sink, and network life time.